The magnetic orientation of the Antarctic amphipod Gondogeneia antarctica is cancelled by very weak radiofrequency fields - Tomanova, K; Vacha, M (The Journal of experimental biology, 2016)
Studies on weak man-made radiofrequency (RF) electromagnetic fields affecting animal magnetoreception aim for a better understanding of the reception mechanism and also point to a new phenomenon having possible consequences in ecology and environmental protection. RF impacts on magnetic compasses have recently been demonstrated in migratory birds and other vertebrates. We set out to investigate the effect of RF on the magnetic orientation of the Antarctic krill species Gondogeneia antarctica, a small marine crustacean widespread along the Antarctic littoral line. Here, we show that upon release, G. antarctica (held under laboratory conditions) escaped in the magnetically seaward direction along the magnetic sea-land axis (y-axis) of the home beach. However, the animals were disoriented after being exposed to RF. Orientation was lost not only in an RF field with a magnetic flux density of 20 nT, as expected according to the literature, but even under the 2 nT originally intended as a control. Our results extend recent findings of the extraordinary sensitivity of animal magnetoreception to weak RF fields in marine invertebrates.
Keywords: rádiové vlny; Larmor frequency; Amphipoda; Magnetoreception; Magnetic Fields; orientace; Radical pair mechanism; zvířata; Antarktida; Radio Waves; Orientation; Narrow-band magnetic field; Antarctic Regions; magnetické pole; Animals